2021
DOI: 10.1037/cap0000273
|View full text |Cite
|
Sign up to set email alerts
|

Children’s mental health problems during the initial emergence of COVID-19.

Abstract: On March 11, 2020, the World Health Organization (WHO) declared COVID-19 a global health pandemic. The impact of COVID-19 on mental health has received widespread attention, but almost no longitudinal studies exist that examine changes in children's mental health during its initial emergence. Using a regression discontinuity natural experiment via a longitudinal cohort design, the present study examines trajectories of children's mental health from December 2019 to March 2020. Participants were 231 children (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…These major stressors have resulted in widespread emotional distress and increased prevalence of mental illness ( Cooke et al, 2020 ). Indeed, stressors emerging from the COVID-19 pandemic are associated with increased psychological distress, anxiety, and depression for young people ( Li and Leung, 2020 ; Singh et al, 2020 ; Browne et al, 2021b ), parents and other caregivers of children ( Wade et al, 2021 ), and the general population ( Xiong et al, 2020 ). Disasters can deprive and drain one’s personal and mental resources, and the imposition of public health precautions can result in a dwindling of one’s network of support ( Aten et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These major stressors have resulted in widespread emotional distress and increased prevalence of mental illness ( Cooke et al, 2020 ). Indeed, stressors emerging from the COVID-19 pandemic are associated with increased psychological distress, anxiety, and depression for young people ( Li and Leung, 2020 ; Singh et al, 2020 ; Browne et al, 2021b ), parents and other caregivers of children ( Wade et al, 2021 ), and the general population ( Xiong et al, 2020 ). Disasters can deprive and drain one’s personal and mental resources, and the imposition of public health precautions can result in a dwindling of one’s network of support ( Aten et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study from China reported significant changes in anxiety among adolescents but not children, and no change was identified for depression (67). In a Canadian study, significant impact on emotional and behavioural problems was detected for male children enrolled in early childhood education, but not females (59). A study from Australia reported no differences in adolescents' reports on negative affect, nor positive affect, during the pandemic as compared to a baseline period (57).…”
Section: (Continued)mentioning
confidence: 93%
“…The scoping review discovered 15 longitudinal studies (Table 3), which involved repeated measures over time and provide stronger evidence to address the question of impact on mental health. Five longitudinal studies involved children (51,55,56,58,59), nine involved adolescents (53,54,57,(60)(61)(62)(63)(64)(65) and one involved children and adolescents (52). Most of the studies indicated negative impact of the pandemic on mental health, including increased symptoms of depression (60,63,64,66), anxiety (60,63,64,67), loneliness (63), psychological distress (51,53,65), hyperactivity and impulsivity (55), and emotional and behavioural problems (59), as well as reductions in emotional regulation (55), happiness and positive emotions China, Asia "To assess the prevalence of two specific mental symptoms, anxiety, and depression, and their socio-demographic correlates among adolescents in the Chinese population during the COVID-19 outbreak.…”
Section: Has the Covid-19 Pandemic And Societal Infection Control Measures Impacted Child And Adolescent Mental Health?mentioning
confidence: 99%
See 1 more Smart Citation
“…21 This is further compounded by the lack of knowledge regarding the impact of EMs on the potentially more vulnerable proportion of children (1 in 5) 22 with pre-existing MH disorders as well as children with neurodevelopmental disorders (NDD) diagnoses (ie, autism spectrum disorder (ASD), obsessive-compulsive disorder (OCD), attentiondeficit/hyperactivity disorder (ADHD)) who are 3-6 more times likely to develop MH difficulties. 23 To date, research on the impact of the pandemic has suggested both deleterious [24][25][26][27] and beneficial 26 effects on MH in children with previous MH and/or NDD diagnoses. For example, authors have suggested that children with a previous depression diagnosis may experience exacerbations of feelings of loneliness and despair due to social isolation, whereas youth with social anxiety may experience improvements in MH 28 29 secondary to reduced social exposures.…”
Section: Impacts Of Ems On Mental Health In Children and Adolescentsmentioning
confidence: 99%